Characterization of a thermostable amidase and development of a bioreactor process for lactic acid production - Makhongela, Happy Steven (Centre for Bioprocess Engineering Research, 2014)
This thesis reports studies of the biochemical properties of a newly isolated thermostable amidase from Bacillus sp. RAPc8, and development of a continuous reactor process for the production of a target product. The amidase was cloned and over-expressed in E. coli BL21 strain pNH 223 pLySs by Cameron (2001). Earlier work by Cameron (2001) on the production and purification of the recombinant amidase showed that the enzyme could be produced with high levels of expression in shake-flask culture. Furthermore, preliminary studies have also shown that the molecular weight of the amidase was approximately 35kDa, and that it acts optimally at a temperature and pH of 50°C and 7.2 respectively.